Exploring the Historical Background of the Massacre of Ethnic Chinese in Batavia in 1740 - Sanalin, Livia; Putri, Karenina Melinda; Lestari, Rosdiana Septire; Putra, Purwanto (Universitas Negeri Semarang, 2024)
Before Batavia turned into Jayakarta, there was an ethnic massacre in the Batavia area, namely in 1740. The purpose of writing this article is to find out the background of the history of the massacre of ethnic Chinese that occurred in 1740. The research method used is the historical method or historical method combined with an intradisciplinary strategy involving the social sciences.In 1740, the Chinese community or ethnic Chinese did a lot of trading in the Batavia area around Tanah Abang and Glodok, a name that is now well known by the Indonesian people. At that time, the Company officials who served in Batavia at that time, and the dissatisfaction of the Chinese people with the policies of the VOC government in Batavia which had peaked before the incident, while the political temperature within the Company itself had also begun to heat up, as well as a conflict of interest between Adriaen Valckenier as Governor General and Gustaaf Willem Baron van Imhoff as Chairman of the Raad van Indië. This policy created a problem for the ethnic Chinese community. It caused a lot of dislike for the policy and eventually led to riots and massacres of ethnic Chinese on October 9-11, 1740 which killed more than 10,000 ethnic Chinese, both inside Batavia and in the surrounding area.